Impact of the Supplementation of Exogenous Protease and Carbohydrase on the Metabolizable Energy and Standardized Ileal Amino Acid Digestibility of Soybean Meals in Two Brazilian Regions - DL Silva; FS Dalólio; LV Teixeira; RF Sens; LFT Albino; HS Rostagno (Brazilian Journal of Poultry Science, 2022)
ABSTRACT This study aimed to evaluate the effects of different exogenous protease and carbohydrase in broiler diets on the nitrogen-corrected apparent metabolizable energy (AMEn) and standardized ileal amino acid digestibility (SIAAD) of soybean meals (SBM) in two Brazilian regions (Minas Gerais-MG and Rio Grande do Sul-RS). The total excreta collection of 528 14-d-old chicks was used to determine AMEn in a completely randomized design in a 2 (SBM MG and RS) x 5 (enzyme A, B, C, D and basal diet) + 1 (reference diet, RD) factorial arrangement, totaling 11 treatments, 8 repetitions, and 6 birds per experimental unit. Two experimental treatments (T1 and T6) without enzyme supplementation formulated with SBM MG and RS were used as negative control (NC). The RD without the inclusion of SBM MG and RS was used to correct the nitrogen balance. To determine the SIAAD, ileal content was collected from of broilers and the same experimental design and treatments of the previous trial were used except for the RD, which was replaced with a nitrogen-free diet (NFD) to quantify the excretion of endogenous amino acids. Soybean meal from MG showed the highest levels (p<0.05) of AME and AMEn (3,188 kcal/kg and 2,700 kcal/kg, respectively) in comparison to SBM RS (3,121 kcal/kg and 2,549 kcal/kg, respectively) and, when supplemented with the exogenous enzyme C, also improved the SIAAD (p<0.05), as compared to other enzymes.